Does financial inclusion improve bank performance in the MENA region? Evidence from GCC and non-GCC countries - Hichem Saidi; Abdelaziz Hakimi; Lamia Adili; Helmi Hamdi (Cogent Business & Management)
This paper investigates the effect of financial inclusion (FI) on bank performance (BF) in the Middle East and North Africa (MENA). It uses data relatives to 74 banks from 10 different countries for the years 2010–2021. The empirical study employed a dynamic panel data estimate based on the Generalized Method of Moments in System (GMM in System). The overall empirical evidence suggests that financial inclusion has a positive impact on the performance of banks. We divided the sample into GCC banks and non-GCC banks to compare the output and ascertain whether there was a difference in results between the two groups of countries. Using both return on assets (ROA) and return on equity (ROE), the findings revealed that financial inclusion increased bank performance in the full sample and GCC countries. The results for non-GCC countries demonstrate that while financial inclusion has a favorable and substantial effect on ROA, it has no significant effect on ROE.